O gerenciamento de resultados durante a fase de abertura de capital das empresas que foram listadas na BOVESPA em 2007 - Costa Neto, Francisco Carvalho (2011)
With the evolution of markets, mainly after globalization, investors started to demand more detailed information about the financial reality of organizations. To the extent that the accounting information is introduced in the process of decisions, it starts to have important economic implications to the several agents. This aspect is particularly crucial when one is dealing with an investor who considers investing resources in stock portfolio. The aim of this paper is to identify, through statistical techniques, the possibility of evidence on the existence of Discretionary Accruals concerning the financial statements presented to the Stock Exchange Comission of Brazil (CVM) to those 56 companies listed in São Paulo Stock Market (Bovespa) during the year of 2007. The reference to the Discretionary Accruals were worked on according the techniques developed by Kang and Sivaramakrishnan (1995), aiming at establishing whether such accruals can be found. The levels of Bovespa s Corporate Governance (NM, N1GC e N2GC), in which each company s stock was listed in the Initial Public Offering, were considered, with the goal of investigating if this indicator can have been a decisive factor to the results of Discretionary Accrual. The present study is limited to the public information obtained in CVM website through the program DivEx. The statistical work was developed through the software SPSS. The result of emphirical test shows that possibly Discretionary Accruals could be used by management as positive and negative, and, also, that the accounting treatment is given by different ways for the three levels of Corporate Governance